RPAS ADS-B AND TRAJECTORY CONTROL DATA TRANSMISSION VIA SATELLITE - Grekhov, Andrii; Kondratiuk, Vasil (Proceedings of National Aviation University (archive), 2017)
Purpose: to develop a model of the satellite communication channel for an remotely piloted air system with adaptive modulation and orthogonal frequency division of channels; 2) to calculate the channel parameters with Rayleigh fading and various types of satellite transponder nonlinearity; 3) analyze the effect of fading and the type of nonlinearity on the parameters of the satellite communication channel. Method: MATLAB Simulink software was used to simulate the channel operation. Results: For the first time, based on the IEEE 802.16d standard, a realistic model of the satellite communication channel of an unmanned aerial vehicle was developed, which is used to estimate the channel parameters. The created model takes into account the Rayleigh fading in the downlink and the nonlinearity of the satellite transponder amplifier. Dependences of the signal-to-noise ratio in the terrestrial receiver on the signal-to-noise ratio in the downlink for various types of modulation (BPSK, QPSK, 16QAM, 64QAM) and data transmission rates are obtained. The nonlinearity of satellite amplifiers was analyzed on the basis of a linear model, a cubic polynomial model, a hyperbolic tangential model, the Gorbani model, and the Rapp model. The results for the cubic polynomial model and the hyperbolic tangential model are similar to the linear model, but differ significantly from the Gorbani model and the Rapp model. For the Gorbani and Rapp models, very low values of the signal-to-noise ratio in the receiver are observed. Conclusion: The proposed approach can be considered as a method of estimating the parameters of the satellite communication channel of an unmanned aerial vehicle with fading. It is shown how the type of modulation varies depending on the level of the signal-to-noise ratio and the type of fading. The developed model allows to predict the operation of the channel with Rayleigh fading and can be useful for the design of communication systems.